Updating Marx’s Concept of Alternatives - Peter Ludes (tripleC: Communication, Capitalism & Critique)
The analysis of Marx’s works will be prepared by outlining a more encompassing research project of intergenerational dialogues, in section 1. Section 2 will review Marx’s concept of an alternative, classless society, which was based, e.g., in the projection of rational planning within companies to a national economy - to be revised and updated. Section 3 will discuss how more realistic long-term intergenerational means of orientation and communication of alternatives can emerge. This diagnosis will imply two exemplary and complementary forces calling for alternatives, namely “the perceived risks facing humanity” (Beck) and the enhancement of human rights as global challenges requiring global institutions.